DIAGNOSIS AND MANAGEMENT OF PATIENTS WITH ADRENAL INCIDENTALOMAS: OUR EXPERIENCE - Krstevska, Brankica; Popov, Zhivko (Macedonian Academy of Sciences and Arts, 2022)
Introduction: Adrenal incidentalomas (AIs) are adrenal masses which are incidentally discovered with imaging technology. They are non-functional and functional, benign, and malignant lesions. Aim: We present a 5-year study of diagnostic and follow up of adrenal incidentalomas with special emphasis on their hormonal activity and differentiation from benign to malignant masses. Material and methods: A group of 26 patients with AIs were investigated at the Internal Medical Centre “Srce”. In all patients, clinical examination, CT, and hormonal tests were performed. Results: Of the 26 patients (10 male and 16 female), aged between 25 and 80, the median tumour size was 33 mm, unilateral AIs in 96.1%, located on the right side in 52%, 96% were benign masses, of which 81% were nonfunctional adrenal masses. Non-functional asymptomatic autonomous cortisol secretion tumours were 22.2%, 7.7% were pheochromocytoma, 3.8% was Cushing's syndrome, adrenocortical carcinoma in 3.8%, and Schwannoma in 3.8%. Statistically significant positive correlation was found between HTA and secreting adrenal tumours (r=0.426, p<0.05), and between the post- suppressive level of cortisol and the size of adrenal tumour (r= 0.560, p<0.05). Age, symptoms and DMT2 have statistically significant impact on the prediction of tumour masses larger then 4 cm (p<0.05). 53.8% of patients underwent surgery and the others are followed. In this small study of 26 cases with AIs, 11.5% were benign hypersecreting tumours, and only one patient (3.8%) had a malignant tumour. Appearance of symptoms, age, or tumour masses larger than 4 cm are more likely to be secreting or malignant tumours.
Keywords: adrenal incidentalomas; pheochromocytoma; "autonomous cortisol secretion"; tumour size